Practical Guide to Business Process Reengineering Using Idefo - G., Clarence Feldmann (Addison-Wesley Professional, 2013)
This is the digital version of the printed book (Copyright © 1998). This book answers the call for a concise, comprehensive introduction to IDEF0 and its application in business process reengineering (BPR) efforts. Here is all the essential information about the IDEF0 method, the function analysis portion of the Integration Definition (IDEF) Methods-its definition, basic rules of usage (including the standard language syntax and semantics as contained in the Federal Standard), and lessons learned from many years of application in the real world. The book features examples based on actual models of commercial clients and government agencies. By studying IDEF0 models, readers learn how the method might be applied to the various aspects of enterprise analysis or systems analysis and what goals and benefits are reasonable to expect from its application. IDEF0 is at the heart of the DoD's version of BPR. In the private sector, industrial organizations that may have initially discovered IDEF through one or more government contracts have adopted it as a method for use with their own corporate BPR efforts. Use this book to apply the techniques of this increasingly popular member of the IDEF family of methods! Three Major Elements of the Method: 1. The concepts are at the foundation of IDEF0, and they preserve the logical sense and intention of the model. These concepts answer why one approach is used over another in the application of IDEF0, and they provide the experienced analyst with the rationale for when it may be necessary to bend the rules. 2. The language of IDEF0 is the analyst's means of describing the activities of an enterprise to other analysts, readers, enterprise management and staff, and others. The language is written in graphical box-and-arrow notation on diagram forms that are structured to form IDEF0 models. 3. The pragmatics of IDEF0 provide the engineering procedures and the do's and don'ts for the use of IDEF0. In many cases, the pragmatics are so closely tied to the concepts and language that they are inseparable, and analysts who have attempted to use IDEF0 without employing the pragmatics have typically been unsuccessful. The most common misuses of IDEF0 are illustrated to show the kinds of problems that can occur if the pragmatics are not followed.